Lying to ourselves: rationality, critical reflexivity, and the moral order as ‘structured agency’ - Goodman, Benny (Nursing philosophy, 2016)
A report suggests that United States’ army officers may engage in dishonest reporting regarding their compliance procedures. Similarly, nurses with espoused high ethical standards sometimes fail to live up to them and may do so while deceiving themselves about such practices. Reasons for lapses are complex. However, multitudinous managerial demands arising within ‘technical and instrumental rationality’ may impact on honest decision-making. This paper suggests that compliance processes, which operates within the social structural context of the technical and instrumental rationality manifest as ‘managerialism’, contributes to professional ‘dishonesty’ about lapses in care, sometimes through ‘thoughtlessness’. The need to manage risk, measure, account, and control in order to deliver efficiency, effectiveness, and economy (technical rationality) thus has both unintended and dysfunctional consequences. Meeting compliance requirements may be mediated by factors such as the ‘affect heuristic’ and ‘reflexive deliberations’ as part of the ‘structured agency’ of nurses. It is the complexity of ‘structured agency’ which may explain why some nurses fail to respond to such things as sentinel events, a failure to recognize ‘personal troubles’ as ‘public issues’, a failure which to outsiders who expect rational and professional responses may seem inconceivable. There is a need to understand these processes so that nurses can critique the context in which they work and to move beyond either/or explanations of structure or agency for care failures, and professional dishonesty.